NOVEL-NOVEL BERLATAR MINANGKABAU SEBAGAI MEDIA PEMBENTUKAN KARAKTER ANAK - Armini Arbain; Ronidin Ronidin (Puitika, 2019)
This article is a result of a research about Minangkabau societal ideology which is reflected by the novels written by West Sumatran’s author. The Minangkabau societal ideology can be as a tool to form and to  educate children. Base on the works analyzed, the ideology message was found and became the foundation to form the children character such as keep strugglins, to have empathy to other people, to have responsibility, creative and innovative, the feeling of togetherness, mutual aid and hard work. Therefore, the benefit cannot be neglected that literary works such as novels can be use as one effective media to form and to lead the character of Indonesian children, especially to establish the uniqueness of Indonesia society in global relation. So that, children have to read literary work as the pillar of character education.Keywords      : novel, ideology, character, society, formation